Emotional basis of gender differences in adolescent self-esteem - Gomez-Baya,Diego (2016)
Lower self-esteem in adolescent girls than boys confers greater vulnerability to numerous risks in their development towards social adulthood. This research aimed to study the role of perceived emotional intelligence in self-esteem's gender differences. An anonymous questionnaire was applied to 1791 Spanish adolescents aged between 12 and 17 years old, composed of the Rosenberg self-esteem scale and a reduced version of the Trait Meta-Mood Scale. The results showed that girls presented lower overall self-esteem than boys, as well as lower perceived emotional intelligence. On the one hand, it was found that high perceived emotional attention was related to lower self-esteem in girls; on the other hand, results detected that high perceived emotional attention was linked to higher perceived emotional clarity and repair in boys, which were associated with higher self-esteem. These results suggest the need to design programmes to improve self-esteem in adolescent girls by reducing perceived emotional attention.